2015
DOI: 10.4067/s0718-07052015000100010
|View full text |Cite
|
Sign up to set email alerts
|

Competencias y formación universitaria del educador deportivo en Italia

Abstract: RESUMENLa finalidad de este artículo es comprobar si las competencias de los programas de formación de algunas Facultades de Ciencias Motoras, en Italia, cubren las necesidades de los profesionales deportivos para atender las actividades físicas, recreativas y deportivas de los ciudadanos. Para ello, hemos desarrollado una metodología mixta desde instrumentos cualitativos y cuantitativos, como la entrevista semiestructurada y el cuestionario. Se entrevistó a 20 entrenadores y 3 responsables de proyectos de int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…As for Factor 3-learning contents and physical activities-both groups considered a lot the training support received for learning how to use play as a didactic resource and teaching content, as well as for understanding the basics of school sport initiation. There were some slightly higher valuations in PETPE because of its exclusive pedagogic approach to the profile and the focus on play and initiation sport as pedagogic resources, using them to address technical and tactical aspects for the sports instruction [37,38,40]. Nevertheless, according to some scholars, sport must be also considered in ITTPE from a socio-critical and equitable perspective [45] in order to compensate for the prevalent competitive sport model reigning in sports federations and fostered on social media [43,46,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Factor 3-learning contents and physical activities-both groups considered a lot the training support received for learning how to use play as a didactic resource and teaching content, as well as for understanding the basics of school sport initiation. There were some slightly higher valuations in PETPE because of its exclusive pedagogic approach to the profile and the focus on play and initiation sport as pedagogic resources, using them to address technical and tactical aspects for the sports instruction [37,38,40]. Nevertheless, according to some scholars, sport must be also considered in ITTPE from a socio-critical and equitable perspective [45] in order to compensate for the prevalent competitive sport model reigning in sports federations and fostered on social media [43,46,63].…”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out by ANECA [1], Campos et al, and Bannister-Tyrrell et al [37,38] highlighted the relevant training aspect of such didactic resources for PETPE. Also, in terms of sport pedagogy, the research carried out by Maulini and Maulini et al [39,40] showed how much the students pursuing PASS valued the technical and tactical knowledge of sport disciplines for their teacher training. But, ITTPE did not consider relevant changes in their sports practices or methodologies [11,41,42].…”
Section: Training Scopes In Initial Teacher Training In Physical Educ...mentioning
confidence: 99%
“…Y son las oportunidades de práctica docente, a modo de simulacros, un marco de intervención desde el que reconocer el grado de desarrollo competencial del alumnado en su desarrollo formativo como docentes. Esta propuesta didáctica parte de competencias específicas y transversales, con la finalidad de promover procesos de empoderamiento profesional en los estudiantes, debido a la conexión entre las prácticas formativas promovidas en el aula y la vinculación con su futura función docente (Maulini, Fraile & Cano, 2015).…”
Section: Introductionunclassified
“…No obstante, encontraron diferencias entre la percepción de desarrollo de este tipo de competencias más en los estudiantes MEPEF que en los CAFyD; estos últimos valorando haber desarrollado más sus competencias específicas a partir de la formación cursada. De forma coincidente, Maulini, Fraile y Cano (2015) encontraron que tales competencias fueron consideradas mejor desarrolladas por los estudiantes MEPEF a partir de la formación que cursaron que en los estudiantes CAFyD, quienes reconocían haber desarrollado en mayor medida las competencias específicas.…”
Section: Las Competencias Emocionales Y Sociales En La Formación Del Profesorado De Efunclassified